A single base substitution in the coding region for neurophysin II associated with familial central diabetes insipidus. - Ito, M (1991)
To elucidate the molecular mechanism of familial central diabetes insipidus (FDI), we sequenced the arginine vasopressin-neurophysin II (AVP-NPII) gene in 2 patients belonging to a pedigree that is consistent with an autosomal dominant mode of inheritance. 10 patients with idiopathic central diabetes insipidus (IDI) and 5 normals were also studied. The AVP-NPII gene, locating on chromosome 20, consists of three exons that encode putative signal peptide, AVP, NPII, and glycoprotein. Using polymerase chain reaction, fragments including the promoter region and all coding regions were amplified from genomic DNA and subjected to direct sequencing. Sequences of 10 patients with IDI were identical with those of normals, while in 2 patients with FDI, a single base substitution was detected in one of two alleles of the AVP-NPII gene, indicating they were heterozygotes for this mutation. It was a G----A transition at nucleotide position 1859 in the second exon, resulting in a substitution of Gly for Ser at amino acid position 57 in the NPII moiety. It was speculated that the mutated AVP-NPII precursor or the mutated NPII molecule, through their conformational changes, might be responsible for AVP deficiency.